PREDIKSI TEKANAN PORI DENGAN DATA SEISMIK 3D DAN DATA LOG SUMUR MENGGUNAKAN METODE EATON (STUDI KASUS DI CEKUNGAN BONAPARTE UTARA) - Tatang Juhatta; Agus Mochamad Ramdhan; Fatkhan Fatkhan (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2017)
Pore pressure prediction has important implications in determining the success of drilling activities. This thesis discusses pore pressure prediction in the northern Bonaparte Basin using wireline log data and 3D seismic interval velocity. The Eaton method is used to predict pore pressure in wells and to construct 3D model of pore pressure. Eaton method is used for pore pressure prediction, overpressure mechanism in the well and 3D model of pore pressure. Pore pressure prediction is determined by effective stress value that is obtained by the analysis of interval check-shot velocity, hydrostatic pressure is assumed to follow the gradient of 0.43 psi/ft and overburden pressure is obtained from density log data. Pore pressure prediction in 3D model is determined from 3D model of effective stress that is generated from average NCT of interval velocity of each well, the hydrostatic pressure is assumed to follow the gradient of 0.43 psi/ft and 3D model of pressure overburden generated from the 3D model density that is obtained from model 3D interval velocity by the result of Gardner transformation. The analyses of pore pressure in the well and 3D model indicate that overpressure occurs in Wangarlu Formation at the depth interval of 2000-2300 m, then it gradually reaches hydrostatic pressure in the Plover Fm. at the depth interval of 3750-3900m. Overpressure is generated by disequilibrium compaction meaning that sediments fail to compact because the expulsion of pore water is inhibited. Compression tectonic activity that occurred in the late Miocene in the north, probably contributes to increase in lateral stress that produces overpressure that spreading laterally to the south of the study area. The results of this study can be applied in the planning of drilling wells including casing design and estimation of mud weight in each depth interval that will be used during drilling.